Determinants of green organizational identity and its impact on green competitive strategy - Desak Nyoman Sri Werastuti Desak; Rumanintya Lisaria Putri; Mayasari Mayasari; Rizka Wahyuni Amelia; Purwanti; Eko Wahyono; Sriyono; Juliana Carolina Kilmanun; A. Nururrochman Hidayatulloh; Agung Sutoto (Accounting Department, Faculty of Business and Economics, Universitas Islam Indonesia, 2023)
This study aims to examine the effect of green intellectual capital and organizational environmental management on green organizational identity and its impact on the green competitive strategy. In this study, green intellectual capital is represented by green human capital, green structural capital, and green relational capital. Meanwhile, the organization's environmental management is represented by an environmental-oriented organizational culture, environmental-oriented leadership, and environmental-oriented capabilities. This study applies a survey that is distributed to 170 respondents who have managerial positions. The sample selection for functional is that respondents have influence and experience in the organization where the respondent works. The number of questionnaires that were successfully returned from the respondents was 146 pieces. From the results of hypothesis testing, it is known that green human capital and environmentally oriented culture have a significant positive effect on green organizational identity. Meanwhile, green structural capital, green relational capital, environmentally oriented leadership, and environmentally oriented abilities do not affect green organizational identity. Green structural capital and green relational capital have a significant positive effect on the green competitive strategy. In contrast, green human capital, environmentally oriented culture, environmental-oriented leadership, and environmental-oriented abilities, green organizational identity do not affect the green competitive strategy.